Viral testing of 18 consecutive cases of equine serum hepatitis: A prospective study (2014‐2018). (5th December 2018) - Tomlinson, Joy E.; Kapoor, Amit; Kumar, Arvind; Tennant, Bud C.; Laverack, Melissa A.; Beard, Laurie; Delph, Katie; Davis, Elizabeth; Schott II, Harold; Lascola, Kara; Holbrook, Todd C.; Johnson, Philip; et al.
Abstract : Background: Three flaviviruses (equine pegivirus [EPgV]; Theiler's disease–associated virus [TDAV]; non‐primate hepacivirus [NPHV]) and equine parvovirus (EqPV‐H) are present in equine blood products; the TDAV, NPHV, and EqPV‐H have been suggested as potential causes of serum hepatitis. Objective: To determine the prevalence of these viruses in horses with equine serum hepatitis. Animals: Eighteen horses diagnosed with serum hepatitis, enrolled from US referral hospitals. Methods: In the prospective case study, liver, serum, or both samples were tested for EPgV, TDAV, NPHV, and EqPV‐H by PCR. Results: Both liver tissue and serum were tested for 6 cases, serum only for 8 cases, and liver only for 4 cases. Twelve horses received tetanus antitoxin (TAT) 4‐12.7 weeks (median = 8 weeks), 3 horses received commercial equine plasma 6‐8.6 weeks, and 3 horses received allogenic stem cells 6.4‐7.6 weeks before the onset of hepatic failure. All samples were TDAV negative. Two of 14 serum samples were NPHV‐positive. Six of 14 serum samples were EPgV‐positive. All liver samples were NPHV‐negative and EPgV‐negative. EqPV‐H was detected in the serum (N = 8), liver (N = 4), or both samples (N = 6) of all 18 cases. The TAT of the same lot number was available for virologic testing in 10 of 12 TAT‐associated cases, and all 10 samples were EqPV‐H positive. Conclusions and Clinical Importance: We demonstrated EqPV‐H in 18 consecutive cases of serum hepatitis. EPgV, TDAV, and NPHV were not consistently present. This information should encourage blood product manufacturers to test for EqPV‐H and eliminate EqPV‐H–infected horses from their donor herds.